Bivalirudin versus heparin with or without glycoprotein IIb/IIIa inhibitors in patients with STEMI undergoing primary PCI: An updated meta-analysis of 10, 350 patients from five randomized clinical trials. Issue 3 (1st June 2016) - Capodanno, Davide; Gargiulo, Giuseppe; Capranzano, Piera; Mehran, Roxana; Tamburino, Corrado; Stone, Gregg W
Abstract: Aims: To evaluate the impact of bivalirudin versus heparin on efficacy and safety outcomes of ST-segment elevation myocardial infarction (STEMI) patients undergoing primary percutaneous coronary intervention (PCI) and to explore the impact of differential use (bailout vs. routine) of glycoprotein IIb/IIIa inhibitors (GPI). Methods and Results: Five randomized controlled trials encompassing 10, 350 patients were included. Primary efficacy and safety endpoints were all-cause death and major bleeding, respectively. All-cause death at 30 days did not significantly differ with bivalirudin compared to heparin (odds ratio (OR) 0.97, 95% confidence interval (CI) 0.74–1.28; P =0.84). Major bleeding was significantly reduced by bivalirudin compared to heparin (OR 0.58, 95% CI 0.40–0.85; P =0.005). Bivalirudin use was associated with non-significantly different rates of 30-day definite stent thrombosis (ST) (OR 1.71, 95% CI 0.84–3.49; P =0.14), albeit with higher rates of acute ST (OR 3.55, 95% CI 1.67–7.56; P =0.001) and non-significantly different rates of subacute ST (OR 0.86, 95% CI 0.46–1.61; P =0.64). There were non-significant differences in the 30-day rates of reinfarction (OR 1.47, 95% CI 0.94–2.30; P =0.10) and cardiovascular death (OR 0.76, 95% CI 0.56–1.02; P =0.07). There were no significant interactions between bailout versus routine GPI use in the heparin arm for any of the safety or efficacy outcomes (all P interaction >0.10). Conclusions: Bivalirudin compared with heparin was associated with comparable 30-day rates of mortality with reduced major bleeding, at the price of an increased risk of acute ST, with non-significant differences in the overall 30-day rates of ST and reinfarction. Intended use of GPI in the heparin arm did not significantly modify the treatment effects of bivalirudin. Given the important differences between trials, as well as evolution in technique and adjunct pharmacotherapy, further randomized trials are warranted to discriminate whether there are substantial safety and efficacy differences between these agents during primary PCI in STEMI.